Large scale and mesoscale patterns of metabolic activity of epipelagic micro and mesoplankton in the Northeastern Central Atlantic at 21ºN - Hernández-León, S.; Postel, L.; Arístegui, J.; Gómez, M.; Montero, M. F.; Torres Curbelo, Santiago; Almeida, C.; Kühner, E.; Brenning, U.; Hagen, E. (1992)
ROSSBY or planetary waves are large-scale and long period, are generated due to temporal variations in the wind stress curl and they are produced annually in the central North Atlantic\ On the other hand, N^ fixating organisms introduce the largest fraction of new nitrogen in the euphotic zone in tropical waters^ and they must produce important consequences in the dynamics of the oligotrophic ocean. We present the results on plankton metabolism over a 2800 Km east-west section in the tropical North Atlantic Ocean showing a combined effect of Rossby waves and N^ fixating organisms on the valúes of enzymatic activities of plankton in the <200, 200-500 and > 500 /jvn size classes. While biomass valúes show only small increases westward at the surface layer (0-25 m), zooplankton enzymatic activities increases to the west part of the section where large phytoplankton chains were observed. Moreover, it is shown as the micro and mesoplankton index of metabolism at the seasonal thermocline layer, match the wavelength of Rossby waves observed. As higher zooplankton metabolic activity have important consequences in the flux of carbón in the ocean, productivity estimates of this low chlorophyll environments have to be reconsidered in relation to this two factors. 11